Infection control and patient discomfort with an alternative plastic barrier in intraoral digital radiography - Arnon Charuakkra (2018)
© 2016 The Authors. Published by the British Institute of Radiology. Objectives: (1) To compare the efficacy of a commercially available hygienic sheath and an alternative plastic bag in preventing contamination of the imaging plate during intraoral radiography and (2) to compare patient discomfort when using the hygienic sheath and the plastic bag. Methods: 60 sterilized Size 2 imaging plates covered with either the hygienic sheath (n = 30) or the plastic bag (n = 30) were used to simulate digital periapical radiographic examination in 30 volunteer patients. After disinfection, each plate was swabbed. The swabbed medium was then plated on trypticase soy agar and incubated. Bacterial colonies were counted. Patient discomfort was assessed using a visual analogue scale (VAS) score. The comparison of the number of bacterial colonies and VAS scores between the two groups was tested by paired t-test at p < 0.05. Results: There was no significant difference in the number of bacterial colonies between the two groups (p = 0.745). Of all the plates, 10% plates yielded bacterial colonies. The mean count of bacterial colonies for both groups was 10-20 CFU ml -1 . However, there was a significant difference between VAS scores for the two systems (p = 0.000). The mean VAS scores (range 0-10) for patient discomfort for the hygienic sheath group and the plastic bag group were 3.03 and 5.33, respectively. Conclusions: Based on the design of this study, the alternative barrier provided similar results to those commercially available. Regarding the type of barrier envelope, the hygienic sheath induced less discomfort than the plastic bag.